Pengembangan Social Entertainment Metaverse: PataLand di Startup Cube Studio Berbasis Platform Website - Nizar, Syamsul; Roedavan, Rickman; Eriyadi, Mindit (eProceedings of Applied Science, 2024)
Cube Studio is a startup founded in 2020, developing into PT Ruang Teknologi Ilmu Nusantara in 2021. Their innovative response to the COVID-19 pandemic, ViraExpoir, revolutionized the exhibition into an exhibition that can be held virtually via a website platform. Recognizing its potential, Surge proposed a collaboration with Cube Studio to develop PataLand, a metaverse social entertainment platform focused on virtual concerts. Venue and location constraints at conventional concerts often limit the number of visitors who can attend. To overcome this problem, Cube Studio together with Surge developed PataLand which can be accessed easily via the website. PataLand is the resulting solution, a three-dimensional visual platform with multi-platform features. PataLand offers exclusivity in the form of direct communication between fans and artists as well as merchandise sales. Immersive 3D environments, cross-platform features, and gamification ensure fun and engaging PataLand interactions. As of June 1 2024, website-based PataLand has been used by 156 people and 130 of them have registered. Keywords — cross platform, game, concert, metaverse, exhibition